A Retrospective Characterization of Dexmedetomidine-Suspected Fever and Its Consequences in Adult Critically Ill Patients. Issue 9 (September 2022) - Schranz, Emily; Rappaport, Stephen; Groth, Christine; Prasad, Paritosh; Cooper, Kevin; Connor, Kathryn
Background: Current evidence for dexmedetomidine-suspected fever (DSF) is limited. Lack of recognition may lead to costly or potentially harmful interventions for critically ill patients. Objective: The primary objective was to characterize escalations of care related to DSF. Secondary objectives were to describe the incidence, severity, and consequences associated with DSF. Methods: A retrospective review was conducted in critically ill adults who developed fever ≥39°C within 12 h from initiation of dexmedetomidine, with resolution of fever to <39°C within 12 h after discontinuation. The primary outcome was percentage of patients who received an escalation of care due to fever. Secondary outcomes included the percentage of patients who developed a multidrug-resistant organism or Clostridium difficile infection. Results: Eighteen of 3943 patients screened in 4099 encounters met criteria for DSF (0.4%). The majority were white (83.3%), male (66.7%), and underwent cardiac surgery (61.1%). Median (interquartile range [IQR]) time to fever onset and resolution were 5.5 (3.6-7.6) and 1.3 (1.0-2.9) h. Nine patients (50%) underwent infectious workup including antimicrobial initiation (n = 1, 5.6%), broadening of antimicrobials (n = 4, 22.2%), or culture collection (n = 9, 50%). Eleven patients (61.1%) underwent attempted temperature reduction. Twelve patients (66.7%) underwent diagnostic imaging. Incidence of multidrug-resistant organism and C. difficile infection were low (11.1 and 16.7% of fever patients, respectively). Conclusion and Relevance: Incidence of DSF was low and more common in cardiac surgery patients. Unrecognized DSF led to an escalation of care in most patients. Dexmedetomidine exposure should be considered as a potential cause of fever in critically ill adults.